Defective by design: vanadium-substituted iron oxide nanoarchitectures as cation-insertion hosts for electrochemical charge storage1. Issue 22 (14th June 2015) - Chervin, Christopher N.; Ko, Jesse S.; Miller, Bryan W.; Dudek, Lisa; Mansour, Azzam N.; Donakowski, Martin D.; Brintlinger, Todd; Gogotsi, Pavel; Chattopadhyay, Soma; Shibata, Tomohiro; Parker, Joseph F.; Hahn, Benjamin P.; et al.
<x xml:space="preserve">Abstract</x> Defective VFe2Ox aerogels are synthesized to maximize cation vacancies that increase Li+- and Na+-insertion capacity.